Economic and societal impacts of tornadoes - Simmons , Kevin M. (American Meteorological Society, 2011)
Evaluates the National Weather Service's warnings and other efforts to reduce tornado casualties based on statistical analysis of data from sources such as NOAA and the U.S. Census - Provided by publisher.